PENGARUH REKAYASA MODEL PEMBERDAYAAN MASYARAKAT TERHADAP POLA PEMBERIAN ASI DI KABUPATEN BOGOR - Fauzia Djamilus; Sri Wahyuni; Sri Mulyati; Maya Astuti (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2022)
The target for achieving exclusive breastfeeding in 2025 globally is 50%. Exclusive breastfeeding coverage targeted in 2017 is 44%, the achievement of exclusive breastfeeding was only 35.7%. In West Java, the achievement of exclusive breastfeeding in 2016 was 46.4%., In Bogor City, the achievement of exclusive breastfeeding in 2017 was 49.5%. The purpose of the study was to determine the effect of community empowerment engineering on breastfeeding patterns in Bogor Regency. The design used is a Quasi Experiment with a Non-Equivalent Group Design approach. The research population consists of, pregnant women in the third trimester, family assistants, midwives/nurses/nutritionists, cadres with a total sample of 60 segments each.. The intervention provided was an education in 4 segments in the form of breastfeeding education classes. The research area is determined based on the low level of achievement of exclusive breastfeeding. To find out if there is an increase in knowledge about breastfeeding and empowerment and breastfeeding patterns in each segment, it is tested with the Wilcoxon test. To determine the effect of community empowerment engineering on breastfeeding patterns, it was tested and analyzed using the Mann Whitney test. The results showed that there was a significant increase in knowledge of pregnant women, assistants, cadres and health workers after attending education. There is an effect of education on breastfeeding patterns.